STRATEGI PEMASARAN PEMBERDAYAAN BAHAN PANGAN LOKAL PENDORONG UMKM INOVASI KERIPIK MENTHO KACANG DI BOYOLALI - Puput Novita Sarah; Erwin Susiani; Lia Avi Natasya; Ikhwan Priambada Danu Arta; Muhammad Dwi Anwari; Unna Ria Safitri (KRIDA CENDEKIA, 2025)
The city of Boyolali which is located in the province of Central Java or better known as the milk city has many interesting special foods, one of which is Mentho or Lentho. Mentho is one of Boyolali's traditional foods that has a distinctive taste and has great potential to be developed as a regional superior product. However, limitations in marketing strategies cause this product to not be widely known outside the local area. This study aims to analyze the marketing strategies implemented by mentho-producing MSME actors in Boyolali and identify supporting and inhibiting factors in the marketing process. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies of five local MSME actors. The results of the study show that the dominant marketing strategies used are word-of-mouth marketing, simple use of social media, and participation in bazaars and regional events. Supporting factors include the uniqueness of the taste and traditional value of the product, while the inhibiting factors include limited market access, capital, and digital capabilities of MSME actors. This study recommends increasing the capacity of MSME actors in digital marketing in order to grow the local economy sustainably, as well as collaborating with local government agencies to expand the reach of mentho promotion as a culinaryy icon of Boyolali.